Democracy, media and corruption: from global to Portugal (Rivista di Studi e Ricerche sulla criminalità organizzata, 2018)
The subprime crisis in the United States and the sovereign debt crises in Europe in the second decade of the second millennium brought, among other things, a new discussion of the role of the media (mainstream, alternative and social networks) in democratic societies. At the same time, a new typology of phenomena emerges, associated to the use, abuse and control of social networks, due to acts of piracy and technological mechanisms such as algorithms and the use of big data. In this paper, we aim to discuss the orientation changes in the mainstream media since the second decade of the second millennium, in particular the mediatization processes, taking as example the journalistic coverage of corruption events in Portugal.Keywords: Democracy; Media; Corruption; Portugal; Mediatization